HUBUNGAN EXPLOSIVE POWER OTOT LENGAN BAHU DAN KOORDINASI MATA TANGAN DENGAN HASIL SHOOTING PADA TIM BOLABASKET PUTRI SMA 1 KAMPAR - Guswandi, Didik; Juita, Ardiah; ', Ramadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Based on the researcher’s of female basketball team SMAN 1 Kampar, research found the result of shooting basketball was not optimal. It influences physical condition that is explosive power arm-shoulder muscles and hand-eyes coordination. The purpose of this research is to see the correlation between explosive power arm-shoulder muscle with the result of shooting, the correlation hand-eye coordination with the result shooting and the coordination explosive power arm-shoulder muscles with the result of shooting of female basketball team SMAN 1 Kampar. Population in this research is all female basketball team SMAN 1 Kampar amount 12 people. Based on population that is not so large and within the limits the researchers set the whole population is used as a sample. The research sample as many as 12 people. Research instrument used two hand medicine ball put test, throwing a tennis ball catch test and set shoot test. Data were analyzed by product moment correlation. Based on research results, it can be concluded as follows : 1. Shows that there is correlation of explosive power arm-shoulder muscle with the result of shooting which shows correlation rhitung (0,668)> rtabel (0,602) so Ha be accepted. 2 there is correlation hand-eye coordination with the result of shooting, which shows correlation rhitung (0,607)> rtabel (0,602) so Ha be accepted. 3. There is correlation between explosive power arm-shoulder muscles and hand-eyes coordination with the result of, which shows r =0,771 rhitung (0,771)> rtabel (0,602) so Ha be accepted.Key word : explosive power arm-shoulder muscles, hand-eyes coordination, shooting.